Usefulness of genome-wide association studies to identify novel genetic variants underlying the plasma lipoprotein metabolism as risk factors for CAD. Issue 3 (September 2015) - Almontashiri, Naif A.M.; Hannan, Mohammed
الملخص: تتفاعل العوامل البيئية والصحية والجينية لتتسبب في ظهور أمراض القلب التاجية. وتعتبر أمراض القلب التاجية من الأسباب الرئيسة للوفيات حول العالم. وتشمل العوامل التقليدية المسببة لأمراض القلب التاجية عوامل كثيرة من أهمها العمر، وارتفاع ضغط الدم، والسكري، والتدخين، وارتفاع نسبة الدهون في الدم. إن الحفاظ على الدهون في مستوياتها الطبيعية يخفض وبشكل كبير من نسبة الإصابة بأمراض القلب وتصلب الشرايين. وقد صممت دراسات الارتباط على مستوى الجينوم بطريقة غير منحازة للتعرف على الاختلافات في تسلسل الجينوم البشري، التي قد تضع الإنسان في خطر (أو تحميه من) الإصابة بأمراض معقدة، ومتعددة الأسباب الجينية كأمراض القلب التاجية والسكري. في هذه المراجعة لما تم عمله من دراسات حتى الآن، نسلط الضوء ونناقش المستجدات لما أسفر عنه استخدام هذه التقنية في اكتشاف اختلافات متعددة في تسلسل الجينوم التي أظهرت ارتباطا بمستويات الدهون في الجسم (نقص أو زيادة)، وكيف يمكن أن تساعد هذه النتائج في التعرف على أهداف علاجية، قد تستخدم مستقبلا في المساعدة في تخفيض مستويات الكولسترول والدهون المرتفعة في الدم. Abstract: Coronary artery disease (CAD) is a major killer across the world. The pathogenesis of CAD is a construct of multiple predisposing elements, including environmental, health and genetic factors. Traditional risk factors for CAD include age, hypertension, diabetes, smoking, and dyslipidaemia. Optimizing the lipid levels to within the normal range significantly and drastically reduces the risk of coronary atherosclerosis. Genome-wide association studies (GWASs) promise to accurately identifying the variants that increase or decrease the risks of multiple and complex disorders. In this review, we shed light on and discuss the recent GWASs of lipoprotein genetics and how such studies have provided new pathways and pharmacological targets that might enable the control the pathological plasma cholesterol levels.